Research Potential Development of Faculty of Humanities and Social Sciences, Nakhon Pathom Rajabhat University - Namdee, Pinthakorn (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2022)
The purpose of this research was to obtain a model for the development of teachers in writing research results for publication at the national level. This study group were teachers of the Faculty of Humanities and Social Sciences, Nakhon Pathom Rajabhat University who participated in the development of research potential of 10 people. The study method was a participatory action research. Data collection using both quantitative and qualitative methods. The quantitative data analysis were: percentage, mean, standard deviation and the comparison of mean research potential. The results of the research were as follows: Research conditions of the faculty members of the Faculty of Humanities and Social Sciences, Nakhon Pathom Rajabhat University is mostly a single study and write as simple research. A small number of published research works. The results of potential development showed that the teachers participating in the project had research potential. Research quality and attitude towards research after development were higher than before. The model for developing research capacity was awareness raising. Management support such as time, budget, personnel development, workshop, a good sample of research, teaches queries and references, follow-up from management, establish a research consultant clinic (mentoring) and network of researchers.